Impact of Differences in Activities of Kuwaiti Companies on their Attitudes towards the Use of Services of Foreign Auditors - Nabi Alduwaila; Mokhtar M.; Metwally Metwally (Journal of Accounting, Business and Management (JABM), 2008)
A survey covering a random sample of 385 companies in the State of Kuwait was conducted in the state of Kuwait during the months of September-November 2006 to gather their attitudes towards using of services of foreign auditors. The technique of factor analysis was used to model the preference of companies for various strategies. Factor scores were used as predictive variables in a multiple discriminant analysis to find out whether there are any significant differences in the activities of companies towards their attitudes in their using of services of foreign auditors. The statistical results suggest that there is a significant discrimination between the attitudes of Kuwaiti companies towards the importance of services of foreign auditors in the areas of reputation, performance, operation facilities and growth. Kuwaiti companies operating in the Agriculture, Mining and Quarrying Sectors would seem to be using services of foreign auditors under the impression that these services assist them in achieving high rates of growth. Kuwaiti Banks, Finance and Insurance companies would seem to be using services of foreign auditors under the impression that these services assist them in achieving high reputation. Kuwaiti companies in the industrial sector use services of foreign auditors not for the purpose of achieving a high reputation but under the impression that most importantly these services offer them operation facilities. Kuwaiti companies in the service sector use services of foreign auditors under the impression that most importantly, these services assist them achieving a high Performance.